Strategi Guru dalam Pembelajaran Hadis pada Siswa Kelas IX di MTs Nahdlatul Muslimat Surakarta : Penelitian - Siti Rohmahayati; Miftakhul Jannah; Farida Rahmawati; Khonsa Mujahidah; Ngatmin Abbas (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Hadith learning at the junior secondary level faces challenges related to students’ diverse abilities and learning motivation, making appropriate teaching strategies essential. This study aims to describe teachers’ strategies in hadith learning for ninth-grade students at MTs Nahdlatul Muslimat Surakarta, as well as to identify the constraints encountered and the efforts made to overcome them. The research employed a descriptive qualitative approach. Data were collected through interviews with one Al-Qur’an Hadith teacher, the school principal, and five ninth-grade students, supported by documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, with source triangulation to ensure data validity. The findings indicate that teachers implement varied strategies, including step-by-step explanations, question-and-answer sessions, discussions, presentations, and the use of audiovisual media. Additional strategies such as quizzes and games are applied to maintain students’ motivation and engagement. The main constraints include students’ difficulties in memorizing hadith texts and narrators, limited instructional time, varying learning motivation, and limited learning facilities. To address these challenges, teachers apply repetition, group work, individual guidance, appropriate media selection, and motivational reinforcement. These strategies contribute to improving students’ understanding and participation in hadith learning.